Tutorials in complex photonic media - Noginov, Mikhail A. (SPIE Press, 2009)
The field of complex photonic media encompasses many leading-edge areas in physics, chemistry, nanotechnology, materials science, and engineering. In [i]Tutorials in Complex Photonic Media[/i], leading experts have brought together 19 tutorials on breakthroughs in modern optics, such as negative refraction, chiral media, plasmonics, photonic crystals, and organic photonics.
Keywords: Photonics.; Photonic crystals.; Metamaterials.; elektronické knihy; electronic books